ICT4Scale in Smallholder Agriculture: Contributions and Challenges - Shilomboleni, Helena; Pelletier, Bernard; Gebru, Berhane (USC ANNENBERG PRESS, 2020)
This article presents the main findings from a meta-review study of 15 agricultural development projects that employed a diversity of information and communications technology (ICT) tools in combination with other interventions to scale up innovations in low-income smallholder agriculture, predominately in sub-Saharan Africa. Overall, the study finds that interactive ICT tools and platforms are valuable in their capacity to improve the quality of agricultural extension and climate information services and, as such, can help smallholder farmers better manage predicted risks on the farm and elsewhere in the agriculture sector. The scope of impact in most of these projects, however, was largely premised on the numbers of beneficiaries reached (e.g., with information pertaining to an innovation). The efficacy of scaled-up results to achieve positive, long-lasting livelihood impacts in smallholder agriculture is more complex, and often requires effecting systemwide change on multiple dimensions, e.g., in societal values, institutional arrangements, market relations, and policy decision making. The scaling process here requires long-term attention, even if the impacts are not immediately apparent.